Manajemen Risiko Performance Qualification Of Laminar Air Flow Filling Machine Berdasarkan ISO 31000 : 2018 dalam Meminimalisasi Kontaminasi pada Produk PT. X - Ilham Ashari Wahid; Arief Rahmana (Fakultas Teknik Universitas Tulang Bawang, 2026)
In 2025, viable and non-viable particle testing at point 1 showed bacterial growth and airborne particles exceeding specifications, resulting in production losses of up to IDR 2 billion per day. This research aims to minimize contamination of products during the Performance Qualification of Laminar Air Flow Filling Machine activities.. The results of the study indicate that: 1). There are two types of risks, namely operational risk and financial risk, with operational risks totaling 12 and financial risks totaling 9. 2). To ensure the success of the Performance Qualification (PQ) on the Laminar Air Flow (LAF) Filling Machine, a structured and systematic approach is required in managing various potential risks that could disrupt the effectiveness of the process. 3). Explain the strategy. Mitigation of existing risks through the handling of operational risks that have been discussed. Therefore, the implication of this research is to pay attention to existing risks by evaluating the risks that have been outlined, and for the company related to the Performance Qualification activities of the LAF in Filling Machine, it is recommended that the company implement this Risk Management and apply the proposed risk handling according to the author's recommendations. Keywords: Pharmacy, Performance Qualification LAF, ISO 31000: 2018, Risk Management